Self-Assembled Isoporous Block Copolymer Membranes with Tuned Pore Sizes - Yu, Haizhou; Qiu, Xiaoyan; Nunes, Suzana P.; Peinemann, Klaus-Viktor (Angewandte Chemie International Edition, 2014)
The combination of nonsolvent‐induced phase separation and the self‐assembly of block copolymers can lead to asymmetric membranes with a thin highly ordered isoporous skin layer. The effective pore size of such membranes is usually larger than 15 nm. We reduced the pore size of these membranes by electroless gold deposition. We demonstrate that the pore sizes can be controlled precisely between 3 and 20 nm leading to a tunable sharp size discrimination in filtration processes. Besides fractionation of nanoparticles and biomaterials, controlled drug delivery is an attractive potential application. Golden pores: Membranes with tunable cylindrical pore diameters between 3 and 20 nm were manufactured and tested for nanoparticle separation and controlled delivery of proteins. The pore size was regulated by electroless gold deposition. The precise size discrimination, facile and scalable fabrication processes, and biocompatible characteristics favor potential uses in the purification of nanoscale materials and drug delivery.